A Case Study: How Social Media Advertisement Influences Consumer Behavior Toward a Fast-Food Restaurant - Yee Huei Lok; Oh Zi Jian; Manoj Kumar Chaudhary; Nurin Amni Bt Khairul Azhar; Nurin Zahirah Bt Azizi; Nursyazana Afiqah Bt Azman; Nurul Husna Bt Hassan; Mohd Rohaan; Nidhi Kumari; Daisy Mui Hung Kee (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2024)
Social media has become an increasingly important platform for shaping consumer behavior toward brands. Subsequently, social media is widely utilized and favored in most nations. This study examines the role of social media advertisement in shaping consumer behavior toward McDonald's. A mixed-methods approach was used, consisting of a survey of social media users and an analysis of McDonald's social media presence. The study found a mixed customer response to social media advertising. While a significant portion of respondents expressed initial interest in exploring products or services further after encountering them on social media, the research also identified a segment of customers who were less likely to be swayed by such marketing. The study also highlighted the influence of social media advertising on consumer behavior, particularly purchase decisions (beta = 0.340). However, the effectiveness of these ads likely depends on individual consumer interests and motivations. McDonald's should consider this when tailoring their social media advertising strategies.